Tuberosity Healing after Reverse Shoulder Arthroplasty for Proximal Humerus Fractures: Is there Clinical Improvement? - Barros, Luís Henrique (Rev Bras Ortop (Sao Paulo), 2020)
Objective  To compare the functional results of patients with complex proximal humerus fracture submitted to total shoulder reverse arthroplasty with and without tuberosity healing. The secondary goal was to know the tuberosity healing rate after reverse shoulder arthroplasty with our surgical technique. Methods  A retrospective, cohort type study, with a prospective database collection. In total, 28 patients fulfilled the inclusion criteria: age ≥ 65 years, reverse shoulder arthroplasty for complex proximal humerus fracture (type-3 or -4, according to Neer), and a minimum of 24 months of follow-up. At six months of follow-up, all of the patients were evaluated radiographically for tuberosity, and then they were divided into 2 groups: those with healed tuberosities and those with non-healed tuberosities. A clinical evaluation using the Constant score, active range of motion and the Visual Analog Scale (VAS) at the last follow-up was also performed. Results  Tuberosity healing occurred in 21 patients (76.3%). There were statistically significant differences in the Constant scoring system ( p  < 0.001), forward elevation ( p  = 0.020), internal rotation ( p  = 0.001) and external rotation ( p  = 0.003) when comparing the group of healed tuberosities with the group of non-healed tuberosities. No differences were found regarding the VAS score. Conclusion  Tuberosity healing results in an improvement of the functional outcomes of patients submitted to reverse shoulder arthroplasty as a treatment for complex proximal humeral fractures in the elderly.